Symmetry and performance in middle distance runners - Manning, J. T.; Pickup, L. J. (International Journal of Sports Medicine, 1998)
Deviations from perfect symmetry in paired traits such as ear size and nostril width may indicate developmental instability and/or short-term fluctuations in hormones. In both cases symmetry is thought to be optimal and to indicate high phenotypic quality. The purpose of this work was to determine the relationship between symmetry and performance in middle-distance runners. Fifty male subjects participated in this study. Deviations from perfect bilateral symmetry were measured in seven traits; ear size, nostril width, 2nd to 5th digit length and wrist width. After measurements were made the subjects were ranked for athletic ability and they reported their best 800 metre and 1500 metre times. Symmetric subjects had higher rankings for athletic ability (nostrils, p<0.001 and ears, p< 0.001), lower best 800 metre times (nostrils, p<0.05 and ears, p<0.01) and lower best 1500 metre times (3rd digit, p<0.01 and ears, p<0.05) than asymmetric subjects. This conclusion remained essentially the same after Bonferroni adjustment for multiple tests and when experience and age were controlled for in multiple regression tests. We conclude that symmetry in traits such as nostrils and ears indicates good running ability. It may therefore be useful in predicting the future potential of young athletes.